Perancangan Website sebagai media promosi dan informasi pada CV. Arunika Production - Dzaky Naufal; Rayhan Donovan Fernando (PT Jurnal Cendekia Indonesia, 2025)
Since information technology is developing so quickly, more businesses are using digital media to promote and disseminate information. CV. As a business providing multimedia production services, Arunika Production needs informative and efficient promotional materials to expand its clientele and enhance its reputation. The goal of this project is to create and construct a website that may serve as a promotional and informational tool, showcasing the company's profile, services, portfolio, and internet contacts. The waterfall method, which incorporates the phases of requirements analysis, system design, implementation, and testing, was employed in the creation of this website. PHP with MySQL database support, HTML, CSS, and JavaScript are among the tools utilized in the design process. The study's end product is a dynamic website that provides comprehensive details about CV. Arunika Production and can serve as a more effective channel of communication between the business and its clients. With the use of this website, CV. Arunika Production hopes to boost its online presence, give clients quick access to information, and broaden its online media marketing reach.